Relieving Cellular Energy Stress in Aging, Neurodegenerative, and Metabolic Diseases, SIRT1 as a Therapeutic and Promising Node - Fang, Yang; Wang, Xifeng; Yang, Danying; Lu, Yimei; Wei, Gen; Yu, Wen; Liu, Xing; Zheng, Qingcui; Ying, Jun; Hua, Fuzhou (Frontiers in Aging Neuroscience, 2021)
The intracellular energy state will alter under the influence of physiological or pathological stimuli. In response to this change, cells usually mobilize various molecules and their mechanisms to promote the stability of the intracellular energy state. Mitochondria are the main source of ATP. Previous studies have found that the function of mitochondria is impaired in aging, neurodegenerative diseases, and metabolic diseases, and the damaged mitochondria bring lower ATP production, which further worsens the progression of the disease. Silent information regulator-1 (SIRT1) is a multipotent molecule that participates in the regulation of important biological processes in cells, including cellular metabolism, cell senescence, and inflammation. In this review, we mainly discuss that promoting the expression and activity of SIRT1 contributes to alleviating the energy stress produced by physio-logical and pathological conditions. The review also discusses the mechanism of precise regulation of SIRT1 expression and activity in various dimensions. Finally, according to the characteristics of this mechanism in promoting the recovery of mitochondrial function, the relationship between current pharmacological preparations and aging, neurodegenerative diseases, metabolic diseases, and other diseases was analyzed.